TYPES OF SPEECH ACT USED IN RESEARCH SEMINAR - A Kamariah (Elite : English and Literature Journal, 2013)
AbstractThe objective of this writing is to give a sight on the use of speech act in a formal spoken discourse by the participants of research seminar as well as to discover the types of speech acts used by participants of the research seminar.The writer applied descriptive research design. The population of the research was the members of research seminar consist of examiners and presenter of English Department, Graduate Program UNM, by total sample was 3 people taken through purpossive random sampling. The data were acquired by the used of video recorder and were analyzed based on the theory of Austin and Searle. The results showed that types of speech acts mostly used by the speaker in the research seminar arequestioning and answering. There are some factors affecting the use of speech act, such as speech situation and speaker relation. AbstractTujuan daritulisan iniadalah untuk memberikanpengetahuan mengenaipenggunaantindak tuturdalamwacanalisanresmi olehpesertaseminarpenelitian, sertauntuk menemukanjenistindak tuturyang digunakan olehpeserta seminarpenelitian. Penulismenerapkandesainpenelitian deskriptif. Populasipenelitian ini adalahanggotaseminarpenelitianyang terdiri daripengujidanpresenterdariJurusan Bahasa Inggris, Program PascasarjanaUNM, denganjumlah sampeladalah3orang yang diambilmelaluipurpossiverandom sampling. Datadiperolehmelaluiperekam videodandianalisisberdasarkanteoriAustindanSearle. Hasil penelitian menunjukkan bahwajenistindak tuturyang banyak digunakan olehpembicaradalamseminarpenelitianyaitu jenis bertanya dan menjawab. Ada beberapafaktor yang mempengaruhipenggunaantindak tutur, sepertisituasiberbicara danhubungan antar-pembicara.